Implementasi Metode Analytical Hierarchy Process dalam Sistem Pendukung Keputusan Penerimaan Karyawan Baru - Ryan, Ida Bagus Putu; Widiartha, I Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 4 (2024): JNATIA Vol. 2, No. 4, Agustus 2024DO - 10.24843/JNATIA.2024.v02.i04.p13, 2024)
Decision support system as problem solving for accepting job applicants with objective assessment. This system has the function of getting the best way or solution in providing decisions that require complex calculations, with the best way being provided by mathematical algorithms combined with computing. In this case, the recommendation system will be able to help find a list of permanent employees from a collection of data in the database easily and efficiently. The application of this decision support system cannot be separated from a method that supports it, as applied in this research, namely the Analytical Hierarchy Process (AHP) to run an appropriate algorithm with weighting for many criterias at the system. Using this method to develop a recommendation system will be in accordance with the aim of creating a system for determining decisions for prospective employees in a business element.